2014
DOI: 10.1590/s0100-69162014000600018
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical simulation parameters for drying of cassava starch pellets

Abstract: Based on experimental tests, it was obtained the equations for drying, equilibrium moisture content, latent heat of vaporization of water contained in the product and the equation of specific heat of cassava starch pellets, essential parameters for realizing modeling and mathematical simulation of mechanical drying of cassava starch for a new technique proposed, consisting of preformed by pelleting and subsequent artificial drying of starch pellets. Drying tests were conducted in an experimental chamber by var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…must be considered. The thermal conductivity (k) of pearl millet grains (P. americanum) was determined as being between 0.1241 -0.1421 W/(m.°C) [11 % < M < 25 %] (Corrêa et al, 2004); the specific heat (cp) of cassava starch pellets (M. esculenta crantz) was determined as being around 1.5 kJ/(kg.°C) [M = 4 % (w/w)] (Moreno et al 2014); the specific mass (ρ) of corn grains (Z. mays) with M ~ 9 % (w/w) was reported as being around 720 -730 kg/m 3 (Andrade et al, 2004) and thermal diffusivity values (α) have been reported as: 1.64•10 -7 -1.65•10 -7 m 2 /s for cashew almonds (S. mombin) (7.81 % < M < 14.04 %) (Gama et al 2012).…”
Section: Characterization and Determination Of Thermophysical Propertiesmentioning
confidence: 99%
“…must be considered. The thermal conductivity (k) of pearl millet grains (P. americanum) was determined as being between 0.1241 -0.1421 W/(m.°C) [11 % < M < 25 %] (Corrêa et al, 2004); the specific heat (cp) of cassava starch pellets (M. esculenta crantz) was determined as being around 1.5 kJ/(kg.°C) [M = 4 % (w/w)] (Moreno et al 2014); the specific mass (ρ) of corn grains (Z. mays) with M ~ 9 % (w/w) was reported as being around 720 -730 kg/m 3 (Andrade et al, 2004) and thermal diffusivity values (α) have been reported as: 1.64•10 -7 -1.65•10 -7 m 2 /s for cashew almonds (S. mombin) (7.81 % < M < 14.04 %) (Gama et al 2012).…”
Section: Characterization and Determination Of Thermophysical Propertiesmentioning
confidence: 99%